ATRIBUT PRODUK DALAM PEMILIHAN SARANG BURUNG WALET GOLDEN SWALLOW - J. E. Sutanto; Hardianto Kusuma (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
The purpose of this research is to determine “Attributes that are preferred by customers inselecting Golden Swallow bird’s nest products”. The population in this study are actual buyerand potential buyer in Surabaya whom are included in middle to upper economic classes. 69respondents are used as samples using judgmental sampling technique which is part of nonprobabilitiesmethod. Variables used in this research are type of bird’s nest, shape of bird’s nest,and weight of packaging size. This study uses Conjoint analysis. Results indicate that theattributes that costumers preferred in selecting Golden Swallow bird’s nest products are mostlytype of bird’s nest with the level of white bird’s nest, weight of packaging size with the level of250 gram, and shape of bird’s nest with the level of bowl shape.Tujuan penelitian ini adalah untuk mengetahui “Atribut-atribut yang menjadi preferensikonsumen dalam memilih produk sarang burung walet Golden Swallow”. Populasi dalampenelitian ini adalah orang yang pernah membeli sarang burung walet dan orang yang berpotensimembeli sarang burung walet di Surabaya yang termasuk dalam kelas ekonomi menengah keatas. Jumlah sampel yang digunakan sebanyak 69 responden dengan menggunakan metodepengambilan sampel non-probabilitas, dengan menggunakan teknik judgmental sampling.Variabel yang digunakan dalam penelitian ini adalah jenis sarang burung walet, bentuk sarangburung walet, dan ukuran berat kemasan. Penelitian ini menggunakan analisis Konjoin. Hasilpenelitian ini menunjukkan bahwa atribut yang menjadi preferensi konsumen dalam memilihproduk sarang burung walet Golden Swallow secara berturut-turut adalah jenis sarang burungwalet dengan level sarang burung walet putih, ukuran berat kemasan dengan level 250 gram, danbentuk sarang burung walet dengan level bentuk mangkuk.